2005
DOI: 10.1111/j.1475-4754.2005.00218.x
|View full text |Cite
|
Sign up to set email alerts
|

Sienese ‘Archaic’ Majolica: A Technological Study of Ceramic Bodies and Coatings*

Abstract: The aim of the present study is to reconstruct the production technology of Sienese ‘archaic’ majolica in the early decades of the 14th century ad. The integration of archaeological data with archived data revealed the presence of numerous workshops, suggesting that the Sienese tradition of majolica production was well developed up until the end of the 16th century. Sixty‐seven uncoated and coated waste products were analysed. The ceramic bodies were examined by OM, XRDp, SEM–EDS, XRF, ICP–OES, ICP–MS and INAA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…By contrast, Papadopoulou et al 223 used a compact portable m-XRF spectrometer to characterise decorated sherds of Neolithic pottery from Polyplatanos, North Greece with a view to confirming origin and manufacturing techniques. Other studies of a similar nature include those of Fortina et al 224 (glazed ceramics from southern Tuscany), Wang et al 225 (porcelain sherds found at Shangdian and Lidipo sites and dated to the Kin Dynasty) and Wood et al 226 (Abbasid blue and white ware from Iraq), amongst others.…”
Section: Archaeological Cultural Heritage and Forensicmentioning
confidence: 83%
“…By contrast, Papadopoulou et al 223 used a compact portable m-XRF spectrometer to characterise decorated sherds of Neolithic pottery from Polyplatanos, North Greece with a view to confirming origin and manufacturing techniques. Other studies of a similar nature include those of Fortina et al 224 (glazed ceramics from southern Tuscany), Wang et al 225 (porcelain sherds found at Shangdian and Lidipo sites and dated to the Kin Dynasty) and Wood et al 226 (Abbasid blue and white ware from Iraq), amongst others.…”
Section: Archaeological Cultural Heritage and Forensicmentioning
confidence: 83%
“…Samples from the ‘vetrina sparsa’ class, mainly characterized by a fine interface and small newly formed minerals, probably experienced short firing/cooling intervals (Molera et al . 2001); whereas those of the ‘invetriata grezza’ class, with a thicker interface and large newly formed minerals, may have experienced longer firing times and slower cooling rates (Fortina et al . 2005).…”
Section: Comparison and Discussion Of The ‘Vetrina Sparsa’ And ‘Invetmentioning
confidence: 99%
“…In terms of ancient production, it is possible to imagine that beginning from the same clay with a suitable chemical composition, a coarse refinement and/ or a quick firing time could result in a matt effect of the gloss, whereas a fine refinement of the clay, and/or a longer firing time and/or different oxygen fugacity Enamels and glazes of Sienese archaic majolica 27,28 Fully understanding the production technology of this kind of coatings needs not only the chemical and textural study of the coatings but also the observation of the chemical and mineralogical reactions at the interface between the coating and the ceramic body. They are two completely different chemical systems and can easily react with each other, leading to the formation of new mineralogical phases.…”
Section: Archaeometric Studymentioning
confidence: 99%